Women and youth entrepreneurship in sheep fattening: IPSR Innovation Profile - Wamatu, Jane; Zeleke, Muluken; Abiso, Tesfaye; Alemayehu, Lulseged; Ephrem, Nahom (2022)
An approach to improve performance and market orientation in sheep fattening by women and youth facilitated through collection action; to increase their access to training in improved feed and feeding technologies, husbandry, entrepreneurship skills and financial literacy; to enhance participation in market-oriented sheep fattening; and to create an enabling environment by strengthening stakeholder engagement through community-of-practice platforms.